Daily triage audit can improve nurses' triage stratification: A pre–post study. (1st December 2022) - Zaboli, Arian; Sibilio, Serena; Magnarelli, Gabriele; Rella, Eleonora; Fanni Canelles, Massimiliano; Pfeifer, Norbert; Brigo, Francesco; Turcato, Gianni
Abstract: Aims: The objective was to evaluate whether the error rate in the application of the triage system decreased after the introduction of daily auditing, and it was also evaluated if the agreement rate between physician and nurse on triage priority levels increased after the introduction of daily auditing and if the error‐related variables in the pre‐intervention period changed in the post‐intervention period. Design: A quasi‐experimental study was performed with a pre–post design, between June 2019 and June 2021 in one emergency department. Methods: The accuracy and error rate of triage in the pre‐ and post‐intervention period were compared. Univariate and multivariate logistic regression analyses were performed to explore the relationships between the variables related to the error. The comparison between the priority level assigned by the physician and the triage nurse was analysed using Cohen's K. Results: Nine hundred four patients were enrolled in the pre‐intervention period and 869 in the post‐intervention period. The error rate in the pre‐intervention period was 23.3% and in the post‐intervention period was 9.7%. The concordance between the degree of priority expressed by the physician and the nurse varied from a quadratically weighted Cohen's K of 0.447 in the pre‐intervention period to 0.881 in the post‐intervention period. Conclusion: Daily auditing is a clinical procedure that improves the nurse's application of the triage system. Daily auditing has reduced errors by the nurse, improving performance and concordance with the physician. Impact: Triage systems are a key point for the stratification of the priority level of patients and it is therefore evident that they maintain high‐quality standards. Through the practice of daily auditing, not only a reduction in the error rate, which ensures patient safety, but also an improvement in triage performance has been demonstrated. No Patient or Public Contribution: The study did not involve any patients during its conduction.